Konteks Epistemis Pada Wacana Grafiti Kaos "Joger" Bali Dan Implementasi Sebagai Materi Ajar Bahasa Indonesia Kelas XII - Puji Lestari Candra Dewi, Wahyu; , Prof. Dr. Markhamah, M.Hum (2016)
The purpose of this study there were four. (1) to analyze the context of epistemic contained in graffiti discourse shirts "Joger" Bali. (2) to analyze the topic of speech contained in the discourse graffiti shirts "Joger" Bali. (3) To analyze the function of humor found in the discourse of graffiti shirts "Joger" Bali. (4) Designing the implementation of the results of this study as teaching material at KD 3.6. Type of research is descriptive qualitative research. Data collection techniques in this study using techniques of documentation. The data analysis was conducted using the method of unified referential. The research found their epistemic context of political, economic epistemic context, the context of epistemic law, epistemic context of health, social epistemic community context, and the context of epistemic defense and security. The topics in the discourse graffiti shirt "Joger" Bali is a topic: public policy on the issue of political contention between the simple life and the spree Spree, adherence to the rules, the dangers of smoking, be natural in social life, the beauty of peace, balance ritual worship with worship work, and do not hate our fellow human beings. Functions of humor in discourse graffiti is as a means of criticism / social protest, means of communication, and entertainment facilities. The results of the research can be applied in the implementation as well as teaching materials Indonesian high school subjects at KD 3.6 and vocational learning at KD 3.3 contained on graffiti discourse shirts "Joger" Bali but rather enter into KD 3.3 CMS Keywords: the context of epistemic discourse graffiti, shirts Joger Bali, implementation.